Report for the Education Department for the calendar year 1987 - British Virgin Islands. Department of Education and Culture (Department of Education and Culture, British Virgin Islands, 1988)
This report records activities in the field of Education in 1987. It covers the various levels and types of education as well as curriculum development and cultural activities. It also presents enrolment data for all types of schools, by age, sex, and grade, and data on teacher employment and Caribbean Examinations Council (CXC) results.
Keywords: report; calendar